2022
DOI: 10.1186/s12909-022-03985-5
|View full text |Cite
|
Sign up to set email alerts
|

Syrian medical students’ acceptance of peer physical examination and its associating factors: a cross-sectional study

Abstract: Background This study aimed to evaluate the acceptance of Peer Physical Examination (PPE) in middle Eastern society with its associate factors, and PPE acceptance during Covid-19 pandemic. The acceptance of PPE is considered high in multiple studies carried out in the west, but there were nearly no studies investigating the acceptance of PPE in the middle east or low-income countries. Methods A questionnaire was shared through social media with stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…In the last decade, the bulk of the available literature has focused on PPE in the medical college program. Some of these studies were conducted in different countries such as Australia, 11 , 32 Hong Kong, 17 Syria, 18 and other regions in an attempt to help identify different trends in practicing PPE in such extremely different areas.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last decade, the bulk of the available literature has focused on PPE in the medical college program. Some of these studies were conducted in different countries such as Australia, 11 , 32 Hong Kong, 17 Syria, 18 and other regions in an attempt to help identify different trends in practicing PPE in such extremely different areas.…”
Section: Resultsmentioning
confidence: 99%
“… 11 This is congruent with the research, which showed that same-sex pairing of students in examination sessions is preferable to matching students of different genders. 8 , 10 , 18 According to the authors, the outlook is a student self-estimation related to personal attitudes and beliefs, including consideration for religion and culture. The outlook of the respondents was divided into three categories: conservative, liberal, and average (the majority).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations